2007
DOI: 10.1021/mp060122j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of a Peptidic GRP78 Ligand for Cancer Cell-Specific Drug Delivery

Abstract: Major obstacles in the development of new therapeutic anticancer drugs are the low bioavailability of hydrophilic substances as well as the nonspecific toxicity towards healthy tissues. As such celltargeting oligopeptides have emerged as attractive drug delivery vehicles for a variety of different types of cargo. The recently identified peptide Pep42 binds to the glucose-regulated protein 78 (GRP78), which is overexpressed on the cell surface of human cancer cells and internalizes into these cells. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 39 publications
5
108
0
3
Order By: Relevance
“…58 Others found that members of the HSP70 family (including GRP78) on mammalian cells interact with scavenger molecules, which are responsible for the uptake of oxLDL, and lead to a rapid internalization of HSP70 antigens. 59 GRP78 is highly involved in the quality control of LDL receptors, and it associates with apolipoprotein B as part of a complex with other chaperones like GRP94, calreticulin and Erp72.…”
Section: Discussionmentioning
confidence: 99%
“…58 Others found that members of the HSP70 family (including GRP78) on mammalian cells interact with scavenger molecules, which are responsible for the uptake of oxLDL, and lead to a rapid internalization of HSP70 antigens. 59 GRP78 is highly involved in the quality control of LDL receptors, and it associates with apolipoprotein B as part of a complex with other chaperones like GRP94, calreticulin and Erp72.…”
Section: Discussionmentioning
confidence: 99%
“…11 GRP78 has a major role in regulating intracellular protein trafficking, 12 apoptosis, 13,14 cell surface receptor-mediated endocytosis, 15 and in a variety of cells, as a cell surface protein that functions as a receptor. 16 As a cell surface protein, GRP78 binds a number of different ligands.…”
mentioning
confidence: 99%
“…23 For over a decade, investigations have explored the divergent functions of GRP78 in nonmelanocytic malignancies, and have begun to focus on targeting the protein for a variety of therapeutic applications. 15,30 GRP78 expression has been studied in a variety of cancer cell lines, including the breast, melanoma, and prostate. [31][32][33][34] Quantitative analysis of GRP78 shows elevated levels in hepatocellular carcinoma and gastric cancer relative to surrounding nontumor tissue.…”
mentioning
confidence: 99%
“…Such dissociation generates a potent transcription factor for UPR gene expression activating signaling pathways to maintain homeostasis (HOTAMISLIGIL, 2010;PFAFFENBACH;TODD;GLIMCHER, 2008). Induced HSPA5 has been used as possible activation markers of the antiapoptotic and antiproliferative agents in tumor cells creating a mechanism of resistance (KIM et al, 2006;LIU et al, 2007;MILOSZEWSKA et al, 2010;ROSATI et al, 2010;ROUE et al, 2011;TAN et al, 2011). On the other hand, the induction of anti-HSPA5 functions as an apoptotic protein, forming caspase 7 and 12 complexes, keeping them inactive and blocking their proapoptotic function (REDDY et al, 2003).…”
Section: Resultsmentioning
confidence: 99%